Informational differences and entrepreneurial networking among small and medium enterprises in Kampala, Uganda: The mediating role of ecologies of innovation - Mayanja, Samuel; Ntayi, Joseph M.; Munene, J.C.; Balunywa, Waswa; Sserwanga, Arthur; Kagaari, James R.K. (Cogent Business & Management, 2019)
This paper examines the mediating role of ecologies of innovation in the relationship between informational differences and entrepreneurial networking among small and medium enterprises (SMEs) in Kampala, Uganda. To empirically validate the conceptual model and test the hypothesized relationships, the authors collected data from a sample of 228 SMEs in Kampala district, Uganda purposefully selected for this study. A cross-sectional survey design was adopted, and data were analysed using SPSS/20 and AMOS version 23. The findings exhibit a full mediation of ecologies of innovation in the relationship between informational differences and entrepreneurial networking among SMEs. Besides, informational differences and entrepreneurial networking are insignificantly related. There were, however, some limitations: as the study was cross-sectional in nature, it was difficult to trace the process of interactions among employees especially, how they attach meaning to information and entrepreneurial networking patterns over time;—the study was conducted in Kampala district among trade, manufacturing, and services sectors only. The implication is that entrepreneurial networking can only be explained and predicted through ecologies of innovation. The study recommends that SME owners/ managers need to fully understand and facilitate ecologies of innovation for employees to interact and attach meaning to information. This research contributes to the literature on mediation of ecologies of innovation between informational differences and entrepreneurial networking through its empirical findings of the hypothesized relationships. It theoretically contributes to existing knowledge by integrating complexity systems leadership theory.
Keywords: Informational differences; Ecologies of innovation; Entrepreneurial networking; SMEs; Complexity